Transfer of English MLU in the Form of Acronym to PSP - Piotrowska-Oberda, Ewa (Respectus Philologicus, 2004)
This article presents the relationship between multi-word lexical units (MLUs) and acronyms in view of internal and external borrowing. To reconstruct any regularity in transferring some multi-word lexical units as acronyms from and to language for general purposes (LGP) and language for special purposes (LSP) the word formation processes are taken into consideration. The quantitative and qualitative analysis covers 100 English acronyms transferred to Polish in Businessman Magazine between 1992–2002. The aim of this analysis is to determine which principles and processes allow for the integration of English acronyms with the Polish vocabulary.